2002
DOI: 10.1136/bmj.324.7328.28
|View full text |Cite
|
Sign up to set email alerts
|

Effect of beta lactam antibiotic use in children on pneumococcal resistance to penicillin: prospective cohort study

Abstract: Objective To examine the relation between use of antibiotics in a cohort of preschool children and nasal carriage of resistant strains of pneumococcus. Design and participants Prospective cohort study over two years of 461 children aged under 4 years living in Canberra, Australia. Main outcome measures Use of drugs, respiratory symptoms, and visits to doctors were documented in a daily diary by parents of the children during 25 months of observation. Isolates of pneumococci, which were cultured from nasal swab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
71
0
2

Year Published

2004
2004
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(76 citation statements)
references
References 13 publications
(10 reference statements)
3
71
0
2
Order By: Relevance
“…34 The immediate hazards of antibiotic use are increased side effects and costs of therapy. 24,35 Recent antibiotic use also increases the likelihood that resistant strains will develop, 9,[36][37][38] and antibiotic resistance has been reported in the absence of previous antibiotic prescriptions, when community use of antibiotics is high. 9,37 Resistance patterns have mirrored temporal and regional patterns of BS antibiotic use.…”
Section: Discussionmentioning
confidence: 99%
“…34 The immediate hazards of antibiotic use are increased side effects and costs of therapy. 24,35 Recent antibiotic use also increases the likelihood that resistant strains will develop, 9,[36][37][38] and antibiotic resistance has been reported in the absence of previous antibiotic prescriptions, when community use of antibiotics is high. 9,37 Resistance patterns have mirrored temporal and regional patterns of BS antibiotic use.…”
Section: Discussionmentioning
confidence: 99%
“…Worldwide, risk factors for the carriage of resistant S. pneumoniae have been well investigated in the last couple of decades [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] and those studies reported that the most influencing factor was the previous use of antibiotics. Unnecessary use of antibiotics had been thought to cause this emergence of antibiotic resistant S. pneumoniae.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] Although debated, several publications have suggested that decreasing antibiotic consumption could contribute to reducing the prevalence of antibiotic-resistant bacteria. [6][7][8][9] Strong evidence suggests that a substantial proportion of antibiotic prescriptions in general practice could be avoided. 10 Respiratory tract infections (RTIs) are the most common reason for antibiotic prescriptions in primary care.…”
Section: Introductionmentioning
confidence: 99%